HAP2(GCS1)-Dependent Gamete Fusion Requires a Positively Charged Carboxy-Terminal Domain - Wong, Julian L.; Leydon, Alexander R.; Johnson, Mark A. (PLOS Genetics, 2010)
Author Summary Recent studies suggest that HAP2(GCS1) is a deeply conserved protein required for gamete membrane fusion, a critical yet poorly understood step in sexual reproduction. HAP2(GCS1) is present in many plant, protist, and animal genomes, and has been shown to be essential for fertilization in Arabidopsis, Chlamydomonas, and Plasmodium. The loss-of-function phenotype in Chlamydomonas suggests a direct role in gamete plasma membrane fusion. HAP2(GCS1) has no known functional domains, making it difficult to predict how it contributes to gamete fusion. We set out to map the critical features of this protein by testing a series of deletions, substitutions, and interspecific chimeras for their ability to rescue the hap2-1 fertilization defect in Arabidopsis. We found that the N-terminus does not tolerate sequence divergence, but the histidine-rich C-terminus does. We propose that the N-terminus of HAP2(GCS1) functions in part by interacting with proteins on the surface of female gametes. The key feature of the C-terminus is positive charge, a characteristic that could favor interactions with the plasma membrane that promote membrane fusion. Our studies provide a description of HAP2(GCS1) functional domains and provide an important framework for defining the role of this essential component of a conserved reproductive mechanism.